PERANAN KEPOLISIAN SATUAN RESERSE KRIMINAL DALAM PEMBERANTASAN PEREDARAN UANG PALSU DI WILAYAH KEPOLISIAN RESOR LABUHANBATU BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG - Triboyono, Agus; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Currency counterfeiting crimes nowadays more rampant in large scale and very worrying where most major impacts posed by this currency counterfeiting crimes that could threaten monetary conditions and national economy. Based on this understanding, the authors formulate three formulation of the problem, namely: First, What is the role of the Police Criminal Investigation Unit Labuhanbatu resort in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu. Secondly, What are the barriers Criminal Investigation Unit in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu. Third, Is the Criminal Investigation Unit of the effort in overcoming obstacles in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the problems to be studied. This research was conducted at the Police Labuhanbatu, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data terier, technical data collection in this study with interviews and literature study then analyzed qualitatively and process data and generate descriptive data and then infer deductively.From the research there are three main issues which can be summarized as follows: First, the role of the Police Criminal Investigation Unit Labuhanbatu resort in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu has not been maximized. Second, barriers Criminal Investigation Unit in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu is in the form of the incomplete legal instruments, and to which the laws here are less clear, law enforcement is still less than professional, which is where the low level of legal awareness and the lack of facilities and infrastructure. Third, efforts Criminal Investigation Unit in overcoming obstacles in combating the crime of counterfeit money circulation in the jurisdiction of Police Labuhanbatu on is through cooperation with the Police another and ask for guidance from the unit on and coordination of relevant institutions, in which the police Criminal Investigation Unit provides socialization to the public about the dangers of counterfeit money and if found immediately report it to the police.Keywords: Role of the Criminal Investigation Unit – Crime - Counterfeit Money